Syngas production from ethanol dry reforming over La and Ce promoted Co/Al2O3 catalysts - Fayaz, Fahim (2019)
Ethanol dry reforming has been emerged as a promising route for converting the renewable ethanol and undesirable greenhouse gas (CO2) to industrially recognized syngas. It can also be used as feedstock for downstream methanol production and Fischer-Tropsch synthesis. However, the carbonaceous deposition during ethanol dry reforming process leads to deactivation of the catalyst. Therefore, the Co-based catalysts were prepared with La and Ce promoters using a wet impregnation method and investigated the physicochemical attributes of 10%Co/Al2O3 as well as evaluated the effect of operating parameters on the catalytic activity of ethanol dry reforming reaction in a quartz fixed-bed reactor. In addition, the effect of different ceria loading (from 2% to 5%) was evaluated for ethanol dry reforming reaction at 973 K and stoichiometric conditions. The results revealed that the 3% Ce-promoted catalyst showed the highest activity and resistance from coke deposition. The 3%Ce-promoted catalyst was compared with 3%La-promoted and unpromoted catalyst at different C2H5OH:CO2 ratios of 2.5:1-1:2.5 and reaction temperature of 923 to 973 K. The 3%La over bare 10%Co/Al2O3 significantly improved the metal dispersion (about 16.6%) and degree of reduction (98.3%). Besides, C2H5OH and CO2 conversions increased up to 150.6% and 55.5%, respectively with growing reaction temperature from 923 to 973 K due to the endothermic character of ethanol dry reforming reaction. In addition, both reactant conversions increased with rising CO2 partial pressure from 20 to 50 kPa for all catalysts while, the decreasing reactant conversions with increasing C2H5OH partial pressure. In ethanol dry reforming runs, H2/CO ratio was always higher than unity due to the presence of side reaction (ethanol dehydrogenation). Irrespective of reaction conditions, La-promoted catalyst seemed to be the best catalyst in terms of both C2H5OH and CO2 conversions. Reactant conversions of catalysts increased in the order; 10%Co/Al2O3 < 3%Ce-10%Co/Al2O3 < 3%La-10%Co/Al2O3 catalysts for all operating conditions. The 10%Co/Al2O3 and 3%La-10%Co/Al2O3 catalysts were examined for longevity tests in ethanol dry reforming and showed that the 3%La-10%Co/Al2O3 catalyst exhibited the high catalytic activity than that of unpromoted catalyst at stoichiometric condition for 72 h and 973 K. Furthermore, La-promoted catalyst was regenerated with three cycles and plotted with time-on-stream at stoichiometric feed composition for 90 h and T = 973 K. The results found that the 3%La exhibited the highest catalytic performance in terms of activity and carbon deposition compared to the counterpart unpromoted catalyst. The heterogeneous nature of deposited carbons (carbon nanofilament and graphite) on spent catalyst surface was evident spent catalyst characterizations. Additionally, the 3% La promoter reduced the carbon formation from 51.49% to 30.06%. Furthermore, from the power law expression found that the activation energy for Ce- and La-promoted catalysts (about 98 kJ mol-1 and La-promoted 93 kJ mol-1, respectively) was smaller compared to unpromoted 10%Co/Al2O3 catalyst (about 108 kJ mol-1). The Langmuir-Hinshelwood rate expressions also suggested that both reactants (C2H5OH and CO2) were associatively adsorbed on single-site of catalyst with corresponding activation energy of about 106 kJ mol-1. This study suggests that the syngas produced over Co-based catalysts with desirable H2/CO ratios could be used directly in Fischer-Tropsch synthesis without the requirement of adjusting feedstock composition.